2019
DOI: 10.1136/esmoopen-2019-000527
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of naldemedine in cancer patients with opioid-induced constipation: a pooled, subgroup analysis of two randomised controlled studies

Abstract: ObjectiveThis post hoc, pooled, subgroup analysis of two randomised studies evaluated baseline characteristics that may influence the efficacy and safety of naldemedine in patients with opioid-induced constipation (OIC) and cancer.MethodsData for patients who received 0.2 mg naldemedine or placebo were pooled from randomised, placebo-controlled, phase IIb and phase III studies. Proportions of spontaneous bowel movement (SBM) responders and patients with diarrhoea were assessed for each treatment group. For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
20
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 16 publications
9
20
0
1
Order By: Relevance
“…It is anticipated that a limited opioid withdrawal response inside the intestinal tract could result from this inhibition by NAL administration. In phase III clinical trials, a significant difference in the clinical opioid withdrawal scale (COWS) was not observed in patients receiving or not receiving NAL [ 6 , 9 ]. Although COWS is a rating scale evaluating both central and peripheral withdrawal symptoms, it is mainly intended for central withdrawal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…It is anticipated that a limited opioid withdrawal response inside the intestinal tract could result from this inhibition by NAL administration. In phase III clinical trials, a significant difference in the clinical opioid withdrawal scale (COWS) was not observed in patients receiving or not receiving NAL [ 6 , 9 ]. Although COWS is a rating scale evaluating both central and peripheral withdrawal symptoms, it is mainly intended for central withdrawal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Naldemedine was approved for OIC treatment based on the outcomes of this long-term study. Multiple studies show that naldemedine is effective and safe to use in cancer patients as well [ 26 - 27 ].…”
Section: Reviewmentioning
confidence: 99%
“…Greater proportions of SBM responders and patients who experienced diarrhea were observed with naldemedine vs. placebo in all subgroups. Changes from baseline in NRS and COWS scores were similar with naldemedine or placebo in patients with or without brain metastases [35].…”
Section: Studies In Cancer Patientsmentioning
confidence: 73%
“…Although not powered to detect statistically significant differences in treatment effect among subgroups, this study demonstrated that naldemedine appeared to benefit cancer patients with OIC and cancer, irrespective of baseline characteristics, and did not seem to affect analgesia or withdrawal even in patients with potential BBB disruptions. Baseline characteristics did not appear to affect the incidence of diarrhea in patients who received naldemedine [35].…”
Section: Studies In Cancer Patientsmentioning
confidence: 82%
See 1 more Smart Citation